CLINICAL EVALUATION OF APAMARGA PRATI-SHARANIYA (TEEKSHNA) KSHARA (LOCAL APPLICATION) HARITAKI CHURNA IN THE MANAGEMENT OF ARSHA (HEMORRHOIDS) - Barik LD; Debnath SK; Sahu DS; Hazra J (International Journal of Ayurveda and Pharma Research, 2020)
Arsha (Hemorrhoids) is one of the most common conditions affecting peoples since time immemorial. The prevalence is equal in both sexes, peaks between the ages of 45 and 65 and declining thereafter. The main cause of hemorrhoids is constipation over a prolonged period of time and has to strain to pass stools, it can damage the lining of anal canal. Sushruta the Father of Surgery advocated four method of treatment of Arsha, which are Bheshaja, Kshara, Agni and Shastra. Under Sushrutas operative procedure local application of Pratisharaniya Kshara in the prolapse piles mass helps to reduce pile mass effectively (Ref.Su.Chi.6). It is safe, cheap, effective, simple, easily approachable procedure and ambulatory treatment and the patients acceptability is good to overcome such problem. Aims & Objective is to evaluate the clinical efficacy of Apamarga Pratisharaniya teekshna kshara in the management of Arsha. & to evaluate the safety of Apamarga Pratisharaniya teekshna kshara in the management of Arsha. Material and Methods: 30 patients were enrolled for the study within a period of one year and Teekshna pratisharaniya kshara was applied on piles mass intra anally under operative procedure with the help of a instrument proctoscope. Observation and result: Reduction in the piles mass evident by Inspection/ proctoscopy /Visual perception was observed remarkably.Bleeding and pain were also reduced remarkably in all the piles patient. 100% relief in bleeding, reduction of pile mass and total reduction in size of pile mass was recorded. Conclusion: Recently these Oldest technique advocated by Sushruta have been proven to be most effective and free from post-operative complications.